Sodium-ion battery negative electrode material and preparation method thereof, sodium-ion battery and power-related equipment

By using P-123 and F-127 copolymers to form a graded carbon sphere structure and using thiazole compounds to coat and doplate, the problems of low specific capacity and poor circulation stability of sodium ion battery hard carbon materials at high magnification are solved. It achieves efficient electrochemical performance and long cycle life.

CN119390049AInactive Publication Date: 2025-02-07GUIZHOU WEIFANG ENERGY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518906.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery hard carbon materials have low specific capacity at high magnification, poor circulation stability, and auxiliary additives are expensive, making it difficult to meet the needs of efficient energy storage.

Method used

P-123 and F-127 copolymers are used as soft templates for hollow graded carbon sphere precursors, and graded carbon sphere structures are formed through hydrothermal treatment, and coated and doped with thiazoles to improve the electron transport capability and circulation of the material. stability.

Benefits of technology

The excellent electrochemical performance of the negative electrode material of sodium ion battery at high magnification is achieved, which extends the cycle life of the material and reduces the cost of auxiliary additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390049A_ABST
    Figure CN119390049A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-ion battery negative electrode material and a preparation method thereof, a sodium-ion battery and electric equipment, and relates to the technical field of sodium-ion battery negative electrode materials. The preparation method of the sodium ion battery negative electrode material comprises the following steps: mixing organic acid, organic amine and water to obtain a solution A, and mixing an additive, a P-123 copolymer, an F-127 copolymer and water to obtain a solution B; mixing the solution A and the solution B to obtain a solution C; carrying out hydrothermal treatment on the solution C, and carrying out solid-liquid separation to obtain a hollow graded carbon sphere precursor; mixing the hollow graded carbon sphere precursor, a thiazole compound and an organic solvent to obtain a mixed material; and roasting the mixed material in a protective atmosphere. A P-123 copolymer and an F-127 copolymer are used as soft template agents of a hollow graded carbon sphere precursor, and a thiazole compound is used for doping and coating heteroatoms, so that the sodium ion battery negative electrode material with ultra-long cycle capacity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a negative electrode material for sodium ion batteries and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art

[0002] Sodium-ion batteries are a complement to lithium-ion batteries for grid-scale energy storage applications. Due to their low cost, safety, and potential for a sustainable supply chain, tremendous research efforts have been made in the past decade to develop hard carbon anode materials for sodium-ion batteries.

[0003] However, hard carbon materials currently face problems such as poor rate performance and poor long cycle life. In the face of these problems, researchers have adopted a series of methods such as heteroatom doping and coating, nano-metal particle attachment, and in-situ etching to improve their specific capacity and cycle stability. However, they still face problems such as low specific capacity at high rates, poor long cycle ability, and expensive various effective auxiliary additives.

[0004] In view of this, the need to develop a sodium ion battery negative electrode material that can have good electrochemical performance at high rates has become a current development difficulty. Summary of the invention

[0005] The purpose of this application is to provide a sodium ion battery negative electrode material and a preparation method thereof, a sodium ion battery and electrical equipment to solve the above problems.

[0006] To achieve the above objectives, the present application provides a first aspect of a method for preparing a negative electrode material for a sodium ion battery, comprising:

[0007] The organic acid, the organic amine and water are first mixed to obtain a solution A, and the additive, the template agent and water are second mixed to obtain a solution B;

[0008] Mixing the solution A and the solution B for the third time to obtain a solution C;

[0009] The solution C is subjected to hydrothermal treatment and solid-liquid separation to obtain a hollow hierarchical carbon sphere precursor;

[0010] The hollow graded carbon sphere precursor, the thiazole compound and the organic solvent are mixed for the fourth time to obtain a mixed material;

[0011] Under a protective atmosphere, the mixed material is calcined to obtain a negative electrode material for a sodium ion battery;

[0012] The templates include P-123 copolymer and F-127 copolymer.

[0013] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0014] A. The organic acid includes benzoic acid;

[0015] B. The organic amine includes tetraethylenepentamine.

[0016] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0017] A. The thiazole compound includes one or more of ethyl (2-amino-4-thiazolyl)acetate, 2,4-thiazolidinedione, 2-mercaptothiazoline, thiazole-4-carboxylic acid, and 2-amino-5-methylthiazole;

[0018] B. the additive includes sodium hexadecenoate;

[0019] C. The organic solvent includes ethanol.

[0020] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0021] A. The solid-to-liquid ratio of the organic acid, the organic amine and the water in the solution A is 1.2g-1.6g:1g:100mL-120mL;

[0022] B. The solid-to-liquid ratio of the additive, the P-123 copolymer, the F-127 copolymer, and the water in the solution B is 0.13g-0.15g: 0.09g: 0.09-0.12g: 50mL-60mL;

[0023] C. The mass ratio of the solution A to the solution B is 2:1-1.2;

[0024] D. The solid-liquid ratio of the hollow graded carbon sphere precursor, the thiazole compound, and the organic solvent is 1g: 0.15g-0.25g: 10mL-12mL;

[0025] E. The protective gas in the protective atmosphere includes argon.

[0026] Optionally, the heating rate of the hydrothermal treatment is 5°C / min-10°C / min, the end temperature is 140°C-160°C, and the insulation time is 6h-10h.

[0027] Optionally, the roasting includes a first roasting, a second roasting and a third roasting performed sequentially;

[0028] The first calcination has a heating rate of 5°C / min-10°C / min, an end point temperature of 600°C-700°C, and a holding time of 4h-6h;

[0029] The heating rate of the second calcination is 5°C / min-10°C / min, the end temperature is 1100°C-1300°C, and the holding time is 0.5h-1h;

[0030] The cooling rate of the third calcination is 5°C / min-10°C / min, the end temperature is 1000°C-1200°C, and the holding time is 2h-4h.

[0031] A second aspect of the present application provides a sodium ion battery negative electrode material, which is prepared by the preparation method of the sodium ion battery negative electrode material.

[0032] Optionally, the diameter of the sodium ion battery negative electrode material is 10nm-10μm.

[0033] A third aspect of the present application provides a sodium ion battery, comprising the sodium ion battery negative electrode material.

[0034] A fourth aspect of the present application provides an electrical device, including the sodium ion battery.

[0035] Compared with the prior art, the beneficial effects of this application include:

[0036] The preparation method of the negative electrode material of the sodium ion battery provided by the present application adopts P-123 copolymer and F-127 copolymer as soft template agents of the hollow graded carbon sphere precursor. Since the chain lengths of the P-123 copolymer and the F-127 copolymer are different, the chain length of the copolymer determines the size of the carbon sphere. The P-123 copolymer is easy to form a small core due to its short chain, and the F-127 copolymer forms a large core due to its long chain. During the hydrothermal treatment process, the organic amine will decompose to produce aldehyde substances. After the aldehyde substances are subjected to a dehydration reaction under acidic conditions, unsaturated ketone substances can be obtained, which will produce polymerization by themselves to form polymers of different lengths. In addition, the organic acid will also react with Aldehyde substances undergo aldol condensation reaction and then condense into a stable carbon layer structure. As the hydrothermal treatment proceeds, the soft template will gradually hydrolyze and be released, thereby producing a hollow hierarchical carbon sphere structure. The hollow hierarchical carbon sphere precursor is then coated with a thiazole compound by calcination. The N and S heteroatoms in the thiazole compound can also dope the hollow hierarchical carbon sphere precursor, providing additional active sites on the surface of the hierarchical carbon sphere. Since the thiazole compound can be well dissolved in organic solvents, it can be well and evenly attached to the hollow hierarchical carbon sphere precursor, achieving a good coating effect, which is beneficial to the rapid transmission of electrons in the material and increases its rate performance.

[0037] The sodium ion battery negative electrode material provided in the present application has a graded hollow carbon sphere structure of different sizes, and the surface of the hollow carbon sphere is rich in pore structure, which is conducive to the infiltration of electrolyte and ion diffusion.

[0038] The sodium ion battery provided in the present application has an anode material with excellent high-rate performance and small attenuation during long-cycle charge and discharge, which plays a key role in improving the rate performance of the entire battery.

[0039] The electrical equipment provided in this application has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0041] Figure 1 This is a scanning electron microscope image of the sodium ion battery negative electrode material HCS-1 prepared in Example 1;

[0042] Figure 2 This is a graph showing the N and S element analysis in the XPS of the sodium ion battery negative electrode material HCS-1 prepared in Example 1;

[0043] Figure 3 This is a graph showing the electrochemical performance of the sodium ion battery prepared in Example 1 at a current density of 10 A / g;

[0044] Figure 4 This is a graph showing the electrochemical performance of the sodium ion battery prepared in Example 1 at a current density of 20 A / g;

[0045] Figure 5 The charge and discharge curves of the sodium ion battery prepared in Example 1 at different current densities of 5A / g-20A / g are shown in the figure;

[0046] Figure 6 XRD diagrams of the sodium ion battery negative electrode materials prepared in Comparative Example 1 and Example 1, respectively;

[0047] Figure 7 The Raman spectra of the sodium ion battery negative electrode materials prepared in Comparative Example 1 and Example 1 respectively;

[0048] Figure 8 This is a scanning electron microscope image of the sodium ion battery negative electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0049] As used herein:

[0050] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0051] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0052] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0053] In these examples, parts and percentages are by mass unless otherwise indicated.

[0054] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0055] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0056] The first aspect of the present application provides a method for preparing a negative electrode material for a sodium ion battery, comprising:

[0057] The organic acid, the organic amine and water are first mixed to obtain a solution A, and the additive, the template agent and water are second mixed to obtain a solution B;

[0058] Mixing the solution A and the solution B for the third time to obtain a solution C;

[0059] The solution C is subjected to hydrothermal treatment and solid-liquid separation to obtain a hollow hierarchical carbon sphere precursor;

[0060] The hollow graded carbon sphere precursor, the thiazole compound and the organic solvent are mixed for the fourth time to obtain a mixed material;

[0061] Under a protective atmosphere, the mixed material is calcined to obtain a negative electrode material for a sodium ion battery;

[0062] The templates include P-123 copolymer and F-127 copolymer.

[0063] It should be noted that the P-123 copolymer is a triblock copolymer p123; and the F-127 copolymer is a triblock copolymer F127.

[0064] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0065] A. The organic acid includes benzoic acid;

[0066] B. The organic amine includes tetraethylenepentamine.

[0067] It should be noted that tetraethylenepentamine will decompose to produce formaldehyde in a hydrothermal high temperature environment. After acid or heating treatment, the formaldehyde undergoes a dehydration reaction to obtain unsaturated ketone substances, which are then condensed into a stable carbon layer structure.

[0068] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0069] A. The thiazole compound includes one or more of ethyl (2-amino-4-thiazolyl)acetate, 2,4-thiazolidinedione, 2-mercaptothiazoline, thiazole-4-carboxylic acid, and 2-amino-5-methylthiazole;

[0070] In some embodiments, thiazole compounds include (2-amino-4-thiazolyl) ethyl acetate, which contains two N atoms, two O atoms and one S atom. Since the N and O heteroatoms provide a multi-electron structure, additional active sites are provided on the surface, which is beneficial to the rapid transmission of electrons in the material and increases its rate performance. The S atom has a general effect and will affect the first-cycle coulomb efficiency, resulting in a certain reduction.

[0071] B. the additive includes sodium hexadecenoate;

[0072] C. The organic solvent includes ethanol.

[0073] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:

[0074] A. The solid-to-liquid ratio of the organic acid, the organic amine and the water in the solution A is 1.2g-1.6g:1g:100mL-120mL;

[0075] Optionally, the solid-to-liquid ratio of the organic acid, the organic amine and the water in solution A can be 1.2g:1g:100mL, 1.3g:1g:100mL, 1.4g:1g:100mL, 1.5g:1g:100mL, 1.6g:1g:100mL, 1.2g:1g:110mL, 1.2g:1g:120mL, 1.6g:1g:120mL or a range value between 1.2g-1.6g:1g:100mL-120mL;

[0076] B. The solid-to-liquid ratio of the additive, the P-123 copolymer, the F-127 copolymer, and the water in the solution B is 0.13g-0.15g: 0.09g: 0.09-0.12g: 50mL-60mL;

[0077] Optionally, the solid-to-liquid ratio of the additive, P-123 copolymer, F-127 copolymer, and water in solution B can be 0.13 g: 0.09 g: 0.09: 50 mL, 0.14 g: 0.09 g: 0.09: 50 mL, 0.15 g: 0.09 g: 0.09: 50 mL, 0.13 g: 0.09 g: 0.1: 50 mL, 0.13 g: 0.09 g: 0.1 1: 50mL, 0.13g: 0.09g: 0.12: 50mL, 0.13g: 0.09g: 0.09: 55mL, 0.13g: 0.09g: 0.09: 60mL, 0.15g: 0.09g: 0.12: 60mL or any value between 0.13g-0.15g: 0.09g: 0.09-0.12g: 50mL-60mL;

[0078] C. The mass ratio of the solution A to the solution B is 2:1-1.2;

[0079] Optionally, the mass ratio of solution A to solution B may be 2:1, 2:1.1, 2:1.2 or any value between 2:1 and 1.2;

[0080] D. The solid-liquid ratio of the hollow graded carbon sphere precursor, the thiazole compound, and the organic solvent is 1g: 0.15g-0.25g: 10mL-12mL;

[0081] Optionally, the solid-to-liquid ratio of the hollow hierarchical carbon sphere precursor, the thiazole compound, and the organic solvent can be 1g: 0.15g: 10mL, 1g: 0.2g: 10mL, 1g: 0.25g: 10mL, 1g: 0.15g: 11mL, 1g: 0.15g: 12mL or any value between 1g: 0.15g-0.25g: 10mL-12mL;

[0082] E. The protective gas in the protective atmosphere includes argon.

[0083] In some embodiments, the heating rate of the hydrothermal treatment is 5°C / min-10°C / min, the end temperature is 140°C-160°C, and the holding time is 6h-10h.

[0084] Optionally, the heating rate of the hydrothermal treatment can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min or any value between 5℃ / min-10℃ / min, the end temperature can be 140℃, 150℃, 160℃ or any value between 140℃-160℃, and the holding time can be 6h, 7h, 8h, 9h, 10h or any value between 6h-10h.

[0085] In some embodiments, the calcining includes a first calcination, a second calcination, and a third calcination performed sequentially;

[0086] The first calcination has a heating rate of 5°C / min-10°C / min, an end point temperature of 600°C-700°C, and a holding time of 4h-6h;

[0087] Optionally, the heating rate of the first calcination can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5°C / min-10°C / min, the end temperature can be 600°C, 650°C, 700°C or any value between 600°C-700°C, and the holding time can be 4h, 5h, 6h or any value between 4h-6h;

[0088] The heating rate of the second calcination is 5°C / min-10°C / min, the end temperature is 1100°C-1300°C, and the holding time is 0.5h-1h;

[0089] Optionally, the heating rate of the second calcination can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5°C / min-10°C / min, the end temperature can be 1100°C, 1200°C, 1300°C or any value between 1100°C-1300°C, and the holding time can be 0.5h, 0.8h, 1h or any value between 0.5h-1h;

[0090] The cooling rate of the third calcination is 5°C / min-10°C / min, the end temperature is 1000°C-1200°C, and the holding time is 2h-4h.

[0091] Optionally, the heating rate of the third calcination can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5°C / min-10°C / min, the end temperature can be 1000°C, 1100°C, 1200°C or any value between 1000°C-1200°C, and the holding time can be 0.5h, 0.8h, 1h or any value between 0.5h-1h.

[0092] It should be noted that first, in the low-temperature calcination stage, a soft carbon structure can be formed, and then a plurality of closed-pore structures are formed, which optimizes the residual organic matter on the surface. After heating, a chaotic graphitized structure of varying sizes is formed. The closed pore structure is beneficial to the charge and discharge performance of hard carbon materials at high rates, as well as long cycle performance, because it is not prone to strong expansion effects.

[0093] A second aspect of the present application provides a sodium ion battery negative electrode material, which is prepared by the preparation method of the sodium ion battery negative electrode material.

[0094] In some embodiments, the diameter of the sodium ion battery negative electrode material is 10 nm-10 μm.

[0095] In some embodiments, the diameter of the negative electrode material of the sodium ion battery is 10nm-1μm 。

[0096] A third aspect of the present application provides a sodium ion battery, comprising the sodium ion battery negative electrode material.

[0097] A fourth aspect of the present application provides an electrical device, including the sodium ion battery.

[0098] It should be noted that electrical equipment includes but is not limited to one or more of electric vehicles, electric bicycles, smart home devices, robots, heavy trucks, ships and energy storage systems.

[0099] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0100] Example 1

[0101] A first aspect of the present embodiment provides a sodium ion battery negative electrode material and a preparation method thereof, comprising:

[0102] S1: 4 mmol of benzoic acid and 1.7 mmol of tetraethylenepentamine were mixed and dissolved in 100 mL of deionized water with stirring (800 r / min) to form solution A;

[0103] S2: 0.5 mmol sodium hexadecenoate, 0.09 g P-123 and 0.09 g F-127 were mixed and stirred (800 r / min) and dissolved in 50 mL of deionized water to form solution B, wherein P-123 and F-127 were purchased from Aladdin Reagent;

[0104] S3: slowly introduce solution B into solution A to form solution C;

[0105] S4: After solution C is mixed evenly and forms a light blue emulsion, it is transferred into a 200 mL reactor and heated to 160°C at a heating rate of 5°C / min for 8 hours. After naturally cooling to room temperature, a mixed solution containing a hierarchical carbon sphere precursor is obtained. The mixed solution is centrifuged at high speed (15000r / min) to obtain a hollow hierarchical carbon sphere precursor, the liquid phase is separated and discarded, and the hollow hierarchical carbon sphere precursor is rinsed with deionized water 3 times to obtain a black hierarchical carbon sphere precursor.

[0106] S5: Mix 1 g of black graded carbon sphere precursor with 0.2 g of (2-amino-4-thiazolyl) ethyl acetate, add 10 mL of ethanol, grind evenly, and in a high-temperature tube furnace, heat to 700 ° C at 5 ° C / min under argon atmosphere, hold for 4 hours, then heat to 1300 ° C at a heating rate of 5 ° C / min, hold for 30 minutes, cool to 1000 ° C at 10 ° C / min, hold for 2 hours, and cool naturally to obtain the sodium ion battery negative electrode material HCS-1. The diameter of the sodium ion battery negative electrode material HCS-1 is 10nm-10μm.

[0107] SEM image of HCS-1, a negative electrode material for sodium ion batteries Figure 1 shown.

[0108] The N and S element analysis curves of HCS-1, a negative electrode material for sodium ion batteries, in XPS are as follows: Figure 2 shown.

[0109] A second aspect of this embodiment provides a sodium ion battery, comprising:

[0110] HCS-1, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, the slurry was coated on aluminum foil, vacuum dried at 120°C, and cut into electrode discs with a diameter of 1.6 cm. The electrode discs were assembled into button batteries in a glove box in the order of negative electrode shell, shrapnel, gasket, sodium sheet, glass fiber separator, negative electrode sheet and positive electrode shell.

[0111] The electrochemical performance test curve of the button cell at a current density of 10 A / g is shown in Figure 3 As shown, the electrochemical performance test curve at a current density of 20A / g is as follows Figure 4 As shown, the charge and discharge curves at different current densities of 5A / g-20A / g are as follows Figure 5 shown.

[0112] Example 2

[0113] A first aspect of the present embodiment provides a sodium ion battery negative electrode material and a preparation method thereof, comprising:

[0114] S1: 4 mmol of benzoic acid and 1.7 mmol of tetraethylenepentamine were mixed and dissolved in 100 mL of deionized water with stirring (800 r / min) to form solution A;

[0115] S2: 0.5 mmol sodium hexadecenoate, 0.09 g P-123 and 0.09 g F-127 were mixed and stirred (800 r / min) and dissolved in 50 mL of deionized water to form solution B;

[0116] S3: slowly introduce solution B into solution A to form solution C;

[0117] S4: After solution C is mixed evenly and forms a light blue emulsion, it is transferred into a 200 mL reactor and heated to 160°C at a heating rate of 5°C / min for 8 hours. After naturally cooling to room temperature, a mixed solution containing a hierarchical carbon sphere precursor is obtained. The mixed solution is centrifuged at high speed (15000r / min) to obtain a hollow hierarchical carbon sphere precursor, the liquid phase is separated and discarded, and the hollow hierarchical carbon sphere precursor is rinsed with deionized water 3 times to obtain a black hierarchical carbon sphere precursor.

[0118] S5: Mix 1 g of black graded carbon sphere precursor with 0.2 g of 2,4-thiazolidinedione, add 10 mL of ethanol, grind evenly, and heat to 700 °C at 5 °C / min in a high-temperature tube furnace under argon atmosphere, hold for 4 h, then heat to 1300 °C at a heating rate of 5 °C / min, hold for 30 min, cool to 1000 °C at 10 °C / min, hold for 2 h, and cool naturally to obtain sodium ion battery negative electrode material HCS-2. The diameter of the sodium ion battery negative electrode material HCS-2 is 10 nm-10 μm.

[0119] A second aspect of this embodiment provides a sodium ion battery, comprising:

[0120] HCS-2, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, the slurry was coated on aluminum foil, vacuum dried at 120°C, and cut into electrode discs with a diameter of 1.6 cm. The electrode discs were assembled into button batteries in a glove box in the order of negative electrode shell, shrapnel, gasket, sodium sheet, glass fiber separator, negative electrode sheet and positive electrode shell.

[0121] Example 3

[0122] A first aspect of the present embodiment provides a sodium ion battery negative electrode material and a preparation method thereof, comprising:

[0123] S1: 4 mmol of benzoic acid and 1.7 mmol of tetraethylenepentamine were mixed and dissolved in 100 mL of deionized water with stirring (800 r / min) to form solution A;

[0124] S2: 0.5 mmol sodium hexadecenoate, 0.09 g P-123 and 0.09 g F-127 were mixed and stirred (800 r / min) and dissolved in 50 mL of deionized water to form solution B;

[0125] S3: slowly introduce solution B into solution A to form solution C;

[0126] S4: After solution C is mixed evenly and forms a light blue emulsion, it is transferred into a 200 mL reactor and heated to 160°C at a heating rate of 5°C / min for 8 hours. After naturally cooling to room temperature, a mixed solution containing a hierarchical carbon sphere precursor is obtained. The mixed solution is centrifuged at high speed (15000r / min) to obtain a hollow hierarchical carbon sphere precursor, the liquid phase is separated and discarded, and the hollow hierarchical carbon sphere precursor is rinsed with deionized water 3 times to obtain a black hierarchical carbon sphere precursor.

[0127] S5: Mix 1 g of black graded carbon sphere precursor with 0.2 g of 2-mercaptothiazoline, add 10 mL of ethanol, grind evenly, and heat to 700 ° C at 5 ° C / min in a high-temperature tube furnace under argon atmosphere, hold for 4 hours, then heat to 1300 ° C at a heating rate of 5 ° C / min, hold for 30 minutes, cool to 1000 ° C at 10 ° C / min, hold for 2 hours, and cool naturally to obtain sodium ion battery negative electrode material HCS-3. The diameter of the sodium ion battery negative electrode material HCS-3 is 10nm-10μm.

[0128] A second aspect of this embodiment provides a sodium ion battery, comprising:

[0129] HCS-3, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, the slurry was coated on aluminum foil, vacuum dried at 120°C, and cut into electrode discs with a diameter of 1.6 cm. The electrode discs were assembled into button batteries in a glove box in the order of negative electrode shell, spring sheet, gasket, sodium sheet, glass fiber separator, negative electrode sheet and positive electrode shell.

[0130] Example 4

[0131] A first aspect of the present embodiment provides a sodium ion battery negative electrode material and a preparation method thereof, comprising:

[0132] S1: 4 mmol of benzoic acid and 1.7 mmol of tetraethylenepentamine were mixed and dissolved in 100 mL of deionized water with stirring (800 r / min) to form solution A;

[0133] S2: 0.5 mmol sodium hexadecenoate, 0.09 g P-123 and 0.09 g F-127 were mixed and stirred (800 r / min) and dissolved in 50 mL of deionized water to form solution B;

[0134] S3: slowly introduce solution B into solution A to form solution C;

[0135] S4: After solution C is mixed evenly and forms a light blue emulsion, it is transferred into a 200 mL reactor and heated to 160°C at a heating rate of 5°C / min for 8 hours. After naturally cooling to room temperature, a mixed solution containing a hierarchical carbon sphere precursor is obtained. The mixed solution is centrifuged at high speed (15000r / min) to obtain a hollow hierarchical carbon sphere precursor, the liquid phase is separated and discarded, and the hollow hierarchical carbon sphere precursor is rinsed with deionized water 3 times to obtain a black hierarchical carbon sphere precursor.

[0136] S5: Mix 1 g of black graded carbon sphere precursor with 0.2 g of thiazole-4-carboxylic acid, add 10 mL of ethanol, grind evenly, and heat to 700 ° C at 5 ° C / min in a high-temperature tube furnace under argon atmosphere, hold for 4 hours, then heat to 1300 ° C at a heating rate of 5 ° C / min, hold for 30 minutes, cool to 1000 ° C at 10 ° C / min, hold for 2 hours, and cool naturally to obtain sodium ion battery negative electrode material HCS-4. The diameter of the sodium ion battery negative electrode material HCS-4 is 10nm-10μm.

[0137] A second aspect of this embodiment provides a sodium ion battery, comprising:

[0138] HCS-4, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, the slurry was coated on aluminum foil, vacuum dried at 120°C, and cut into electrode discs with a diameter of 1.6 cm. The electrode discs were assembled into button batteries in a glove box in the order of negative electrode shell, shrapnel, gasket, sodium sheet, glass fiber separator, negative electrode sheet and positive electrode shell.

[0139] Example 5

[0140] A first aspect of the present embodiment provides a sodium ion battery negative electrode material and a preparation method thereof, comprising:

[0141] S1: 4 mmol of benzoic acid and 1.7 mmol of tetraethylenepentamine were mixed and dissolved in 100 mL of deionized water with stirring (800 r / min) to form solution A;

[0142] S2: 0.5 mmol sodium hexadecenoate, 0.09 g P-123 and 0.09 g F-127 were mixed and stirred (800 r / min) and dissolved in 50 mL of deionized water to form solution B;

[0143] S3: slowly introduce solution B into solution A to form solution C;

[0144] S4: After solution C is mixed evenly and forms a light blue emulsion, it is transferred into a 200 mL reactor and heated to 160°C at a heating rate of 5°C / min for 8 hours. After naturally cooling to room temperature, a mixed solution containing a hierarchical carbon sphere precursor is obtained. The mixed solution is centrifuged at high speed (15000r / min) to obtain a hollow hierarchical carbon sphere precursor, the liquid phase is separated and discarded, and the hollow hierarchical carbon sphere precursor is rinsed with deionized water 3 times to obtain a black hierarchical carbon sphere precursor.

[0145] S5: Mix 1 g of black graded carbon sphere precursor with 0.2 g of 2-amino-5-methylthiazole, add 10 mL of ethanol, grind evenly, and heat to 700 ° C at 5 ° C / min in a high-temperature tube furnace under argon atmosphere, hold for 4 hours, then heat to 1300 ° C at a heating rate of 5 ° C / min, hold for 30 minutes, cool to 1000 ° C at 10 ° C / min, hold for 2 hours, and cool naturally to obtain sodium ion battery negative electrode material HCS-5. The diameter of the sodium ion battery negative electrode material HCS-5 is 10nm-10μm.

[0146] A second aspect of this embodiment provides a sodium ion battery, comprising:

[0147] HCS-5, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, the slurry was coated on aluminum foil, vacuum dried at 120°C, and cut into electrode discs with a diameter of 1.6 cm. The electrode discs were assembled into button batteries in a glove box in the order of negative electrode shell, spring sheet, gasket, sodium sheet, glass fiber separator, negative electrode sheet and positive electrode shell.

[0148] Comparative Example 1

[0149] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that no thiazole compound is added to the hollow graded carbon sphere precursor of this comparative example before calcination, and other conditions are consistent with Example 1.

[0150] The XRD test and Raman spectrum test of the sodium ion battery negative electrode material prepared in this comparative example and the sodium ion battery negative electrode material prepared in Example 1 are as follows: Figure 6 , Figure 7 shown.

[0151] Comparative Example 2

[0152] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that no organic acid is added in this comparative example, and other conditions are consistent with Example 1.

[0153] Comparative Example 3

[0154] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that the template agent in this comparative example is only P-123 copolymer, and other conditions are consistent with Example 1.

[0155] The scanning electron microscopy of the sodium ion battery negative electrode material prepared in this comparative example is as follows Figure 8 shown.

[0156] Comparative Example 4

[0157] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that the template agent in this comparative example is only copolymer P-127, and other conditions are consistent with Example 1.

[0158] Comparative Example 5

[0159] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example adopts a one-stage roasting, in a high-temperature tubular furnace, under an argon atmosphere, the temperature is raised to 1300° C. at 5° C. / min, and the holding time is 0.5 h. Other conditions are consistent with Example 1.

[0160] The sodium ion batteries prepared in the above embodiments and comparative examples were subjected to electrochemical performance tests on the Newwell test system, and the test results of the electrochemical performance tests are shown in Table 1. The sodium ion battery negative electrode materials prepared in the embodiments and comparative examples were also subjected to N, S, and O content analysis tests, and the specific test results are shown in Table 2.

[0161] Table 1 Electrochemical performance test

[0162]

[0163] The sodium ion battery negative electrode materials prepared in the examples and comparative examples were also subjected to N, S, and O element content analysis tests. The specific test results are shown in Table 2.

[0164] Table 2 Element content analysis

[0165]

[0166]

[0167] It can be seen from the above tests that the coated material shows excellent long-cycle stability at a high rate. Different element coatings will have different effects on its stability. Among them, N and O elements are beneficial to its charge and discharge performance at a high rate. When only a single template source is used, the material shows a completely different morphology and structure, and the performance difference is large. Because the acidity conditions cannot be achieved and the hierarchical carbon sphere structure cannot be formed, there is no data for comparative example 2. The performance of the hierarchical carbon sphere is the most excellent, which is due to its special hierarchical structure and modification on the surface. In addition, the calcination temperature will have a serious impact on the microstructure of the material.

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0169] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: include: The organic acid, the organic amine and water are first mixed to obtain a solution A, and the additive, the template agent and water are second mixed to obtain a solution B; Mixing the solution A and the solution B for the third time to obtain a solution C; The solution C is subjected to hydrothermal treatment and solid-liquid separation to obtain a hollow hierarchical carbon sphere precursor; The hollow graded carbon sphere precursor, the thiazole compound and the organic solvent are mixed for the fourth time to obtain a mixed material; Under a protective atmosphere, the mixed material is calcined to obtain a negative electrode material for a sodium ion battery; The templates include P-123 copolymer and F-127 copolymer.

2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. The organic acid includes benzoic acid; B. The organic amine includes tetraethylenepentamine.

3. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. The thiazole compound includes one or more of ethyl (2-amino-4-thiazolyl)acetate, 2,4-thiazolidinedione, 2-mercaptothiazoline, thiazole-4-carboxylic acid, and 2-amino-5-methylthiazole; B. the additive includes sodium hexadecenoate; C. The organic solvent includes ethanol.

4. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. The solid-to-liquid ratio of the organic acid, the organic amine and the water in the solution A is 1.2g-1.6g:1g:100mL-120mL; B. The solid-to-liquid ratio of the additive, the P-123 copolymer, the F-127 copolymer, and the water in the solution B is 0.13g-0.15g: 0.09g: 0.09-0.12g: 50mL-60mL; C. The mass ratio of the solution A to the solution B is 2:1-1.2; D. The solid-liquid ratio of the hollow graded carbon sphere precursor, the thiazole compound, and the organic solvent is 1g: 0.15g-0.25g: 10mL-12mL; E. The protective gas in the protective atmosphere includes argon.

5. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The heating rate of the hydrothermal treatment is 5°C / min-10°C / min, the end temperature is 140°C-160°C, and the insulation time is 6h-10h.

6. The method for preparing a negative electrode material for a sodium ion battery according to any one of claims 1 to 5, characterized in that: The roasting includes a first roasting, a second roasting and a third roasting performed sequentially; The first calcination has a heating rate of 5°C / min-10°C / min, an end point temperature of 600°C-700°C, and a holding time of 4h-6h; The heating rate of the second calcination is 5°C / min-10°C / min, the end temperature is 1100°C-1300°C, and the holding time is 0.5h-1h; The cooling rate of the third calcination is 5°C / min-10°C / min, the end temperature is 1000°C-1200°C, and the holding time is 2h-4h.

7. A negative electrode material for a sodium ion battery, characterized in that: The negative electrode material for a sodium ion battery is prepared by the method for preparing the negative electrode material for a sodium ion battery according to any one of claims 1 to 6.

8. The sodium ion battery negative electrode material according to claim 7, characterized in that: The diameter of the sodium ion battery negative electrode material is 10nm-10μm.

9. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode material as described in claim 8.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.